Bulletproof and explosion-proof composite material and preparation process thereof
By combining ultra -high molecular quantitative polyethylene fiber, nano alumina particles, and graphene nanoscopy with high -strength cement base concrete to prepare a bulletproof and explosion -proof composite material, the traditional steel concrete has insufficient protection under high energy impact. The problem realizes stronger protection performance and longer service life.
Patent Information
- Application Number
- CN202411596188.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional reinforced concrete structures have limited protection effects when facing high-energy armor-piercing bombs and explosion impacts, and have problems such as large weight, easy corrosion and short service life.
Adopt advanced materials such as ultra -high molecular measuring polyethylene (UHMWPE) fiber, nano alumina particles, and graphene nanoscopic tablets, combined with high -strength cement base concrete, prepare a bulletproof, explosion -proof composite material through scientific craftsmanship, and coated on the surface Polyurethane layer to improve corrosion resistance.
It has significantly improved the resistance of composite materials, providing stronger bulletproof and explosion -proof performance, extending the service life, and reducing maintenance costs. At the same time, it has conductivity and is suitable for complex safe environments.
Smart Images

Figure CN119371153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a bulletproof and explosion-proof composite material and a preparation process thereof. Background Art
[0002] In modern protection technology, with the continuous upgrading of weapons and equipment, especially the widespread use of high-energy armor-piercing shells and explosives, traditional building materials and protective structures can no longer provide effective protection. This makes the development of new composite materials with stronger bulletproof and explosion-proof properties an urgent need.
[0003] In the prior art, although reinforced concrete structures have certain strength and protective performance, they have the disadvantages of being heavy, prone to corrosion, and easily damaged by high-energy impacts. Rust and fatigue damage of steel bars not only affect the protective performance of the structure, but also shorten the service life of the structure. In addition, the protective effect of traditional reinforced concrete against high-energy explosions and armor-piercing projectiles is limited, and it cannot meet today's increasingly severe safety needs.
[0004] To solve these problems, researchers have begun to explore various new reinforcement materials, such as fiber-reinforced concrete (FRC) and polymer-modified concrete. These materials have improved the tensile strength and crack resistance of concrete to a certain extent. However, existing fiber reinforcement technologies, such as steel fiber and glass fiber, still have problems such as easy corrosion, insufficient durability and lack of toughness, making it difficult to provide long-term and stable protection in extreme environments.
[0005] As a new type of high-performance reinforcing material, ultra-high molecular weight polyethylene (UHMWPE) fiber is gradually being used in various protection fields due to its extremely high tensile strength, good impact resistance and chemical corrosion resistance. UHMWPE fiber is not only lightweight and rust-proof, but can also significantly improve the toughness and penetration resistance of composite materials. Therefore, the application of UHMWPE fiber in concrete reinforcement materials can effectively improve its bulletproof and explosion-proof performance and extend its service life.
[0006] At the same time, the development of nanotechnology has brought new breakthroughs in the protection capabilities of new composite materials. Nanomaterials such as nano-alumina particles and graphene can further improve the overall protection level of composite materials due to their excellent compression resistance, crack resistance and electrical conductivity. In particular, the thermal and electrical conductivity of graphene can effectively disperse the explosion energy in explosion-proof materials and reduce impact damage.
[0007] Therefore, bulletproof and explosion-proof composite materials based on advanced materials such as ultra-high molecular weight polyethylene fibers, nano-alumina particles, and graphene have great application potential. By rationally combining these materials and using scientific processes to prepare them, a composite material with light weight, corrosion resistance, strong durability, and excellent protective performance can be obtained to cope with increasingly complex security threats. Summary of the invention
[0008] In view of this, the object of the present invention is to provide a bulletproof and explosion-proof composite material and a preparation process thereof to solve the above-mentioned problems.
[0009] Based on the above purpose, the present invention provides a bulletproof and explosion-proof composite material and a preparation process thereof.
[0010] A bulletproof and explosion-proof composite material and a preparation process thereof, comprising the following components: Basic materials: high-strength cement-based concrete, as the main structural carrier; Reinforcement material: Ultra-high molecular weight polyethylene short fiber (UHMWPE), which improves the toughness and protective properties of the material; Nano-alumina particles: used to enhance the material's compressive and penetration resistance; Graphene nanosheets: used to improve the conductivity, explosion resistance and heat resistance of materials; Polyurethane coating: used for external coating to prevent the intrusion of moisture and corrosive substances.
[0011] Furthermore, the addition amount of ultra high molecular weight polyethylene short fibers is 0.3% of the weight of concrete.
[0012] Furthermore, the length of the ultra-high molecular weight polyethylene short fibers is 5-10 mm.
[0013] Furthermore, the nano-alumina particles are uniformly dispersed in the concrete.
[0014] Furthermore, the addition amount of graphene nanosheets is 0.05% to 0.1% of the weight of concrete.
[0015] Furthermore, a preparation process of a bulletproof and explosion-proof composite material comprises the following steps: S1. Raw material preparation: select high-strength cement and aggregate, weigh appropriate amounts of ultra-high molecular weight polyethylene short fibers, nano-alumina particles and graphene nanosheets; S2, mixing process: mix cement, aggregate and nano-alumina particles evenly, add water and stir into a slurry; add ultra-high molecular weight polyethylene short fibers and graphene nanosheets into the mixture and stir evenly; S3, mold forming: prepare the mold, apply the release agent, pour the mixed material into the mold, vibrate and exhaust, and ensure the material is dense; S4. Preliminary curing: Leave to stand at 20-25℃ for 24 hours for preliminary curing; S5. Wet curing: After initial curing, carry out wet curing for 7 days; S6, high temperature drying: drying at 50°C; S7. Polyurethane coating treatment: Apply a 0.5-1mm thick polyurethane coating evenly on the surface of the material and cure it at room temperature for 48 hours.
[0016] Furthermore, the mold forming process includes vibrating the mold using a vibration table to remove air bubbles from the material.
[0017] Furthermore, the ambient humidity is maintained during the wet curing process to improve the strength and durability of the material.
[0018] Furthermore, high-temperature drying treatment ensures that the moisture in the material is completely evaporated, thereby improving the hardness and toughness of the material.
[0019] Beneficial effects of the present invention: 1. The composite material of the present invention significantly improves the material's penetration resistance and impact resistance by introducing ultra-high molecular weight polyethylene (UHMWPE) fibers and nano-alumina particles, can effectively resist high-energy armor-piercing bullets and explosion shocks, and ensure its protective effect under extreme conditions. Compared with traditional reinforced concrete, the composite material of the present invention has a lighter weight and is easy to carry and construct. This lightweight feature makes the material have good adaptability in various applications, such as military, construction, and transportation. The UHMWPE fiber used in the composite material has excellent corrosion resistance. Combined with the external protection of the polyurethane coating, it can effectively prevent the intrusion of moisture and other corrosive substances, thereby greatly extending the service life of the material and reducing maintenance costs. The composite material not only has bulletproof and explosion-proof properties, but also can enhance the stability of the material in an electromagnetic interference environment through the conductivity of graphene, which provides the possibility for the application of future intelligent protection systems. The raw materials used in the preparation process of the present invention are all environmentally friendly materials, which meet the requirements of green buildings and sustainable development, and help reduce the impact on the environment. Due to its excellent performance, the composite material can be widely used in military equipment, civil protection facilities, transportation and other fields, and has good market prospects and economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 It is a schematic diagram of the process structure of the present invention; Figure 2 It is a schematic diagram of an armor-piercing incendiary bullet impact test according to an embodiment of the present invention. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] A bulletproof and explosion-proof composite material and a preparation process thereof, comprising the following components: Basic materials: high-strength cement-based concrete, as the main structural carrier; Reinforcement material: Ultra-high molecular weight polyethylene short fiber (UHMWPE), which improves the toughness and protective properties of the material; Nano-alumina particles: used to enhance the material's compressive and penetration resistance; Graphene nanosheets: used to improve the conductivity, explosion resistance and heat resistance of materials; Polyurethane coating: used for external coating to prevent the intrusion of moisture and corrosive substances.
[0024] In a specific embodiment, the addition amount of ultra-high molecular weight polyethylene short fibers is 0.3% of the weight of concrete, the length of the ultra-high molecular weight polyethylene short fibers is 5-10 mm, the nano-alumina particles are uniformly dispersed in the concrete, and the addition amount of graphene nanosheets is 0.05%~0.1% of the weight of concrete.
[0025] Specifically, a preparation process of a bulletproof and explosion-proof composite material comprises the following steps: S1. Raw material preparation: select high-strength cement and aggregate, weigh appropriate amounts of ultra-high molecular weight polyethylene short fibers, nano-alumina particles and graphene nanosheets; S2, mixing process: mix cement, aggregate and nano-alumina particles evenly, add water and stir into a slurry; add ultra-high molecular weight polyethylene short fibers and graphene nanosheets into the mixture and stir evenly; S3, mold forming: prepare the mold, apply the release agent, pour the mixed material into the mold, vibrate and exhaust, and ensure the material is dense; S4. Preliminary curing: Leave to stand at 20-25℃ for 24 hours for preliminary curing; S5. Wet curing: After initial curing, carry out wet curing for 7 days; S6, high temperature drying: drying at 50°C; S7. Polyurethane coating treatment: Apply a 0.5-1mm thick polyurethane coating evenly on the surface of the material and cure it at room temperature for 48 hours.
[0026] Specifically, the mold forming process includes using a vibration table to vibrate the mold to remove bubbles in the material, maintaining the ambient humidity during wet curing to improve the strength and durability of the material, and warm drying to ensure that the moisture in the material is completely evaporated to improve the hardness and toughness of the material.
[0027] Example 1 Material composition Basic material: High-strength cement-based concrete, as the main structural carrier.
[0028] Reinforcement material: Ultra-high molecular weight polyethylene short fiber (UHMWPE), which improves the toughness and protective properties of the material, and the added amount is 0.3% of the weight of concrete.
[0029] Nano-alumina particles: used to enhance the material's compressive and penetration resistance.
[0030] Graphene nanosheets: Improve the conductivity, explosion resistance and heat resistance of materials.
[0031] Polyurethane coating: used for external coating to prevent the intrusion of moisture and corrosive substances.
[0032] Preparation process Raw material preparation: Select high-strength cement and aggregate, and weigh appropriate amounts of ultra-high molecular weight polyethylene short fibers, nano-alumina particles and graphene nanosheets.
[0033] Mixing process: Mix cement, aggregate and nano-alumina particles evenly, add water and stir into a slurry; add ultra-high molecular weight polyethylene short fibers and graphene nanosheets into the mixture and stir evenly.
[0034] Moulding: prepare the mould, apply release agent, pour the mixed material into the mould, use a vibrating table to remove air bubbles and ensure the material is dense.
[0035] Initial curing: Leave it at 20-25℃ for 24 hours for initial curing.
[0036] Wet curing: After initial curing, carry out wet curing for 7 days.
[0037] High temperature drying: Drying is carried out at 50°C to ensure that the moisture in the material is completely evaporated and to improve the hardness and toughness of the material.
[0038] Polyurethane coating treatment: Apply 0.5-1mm thick polyurethane coating evenly on the surface of the material and cure it at room temperature for 48 hours.
[0039] Example 2 Material composition Basic material: High-strength cement-based concrete, as the main structural carrier.
[0040] Reinforcement material: Ultra-high molecular weight polyethylene short fiber (UHMWPE), which improves the toughness and protective properties of the material, and the added amount is 0.2% of the weight of concrete.
[0041] Nano-alumina particles: used to enhance the material's compressive and penetration resistance.
[0042] Graphene nanosheets: Improve the conductivity, explosion resistance and heat resistance of materials.
[0043] Polyurethane coating: used for external coating to prevent the intrusion of moisture and corrosive substances.
[0044] Preparation process Raw material preparation: Select high-strength cement and aggregate, and weigh appropriate amounts of ultra-high molecular weight polyethylene short fibers, nano-alumina particles and graphene nanosheets.
[0045] Mixing process: Mix cement, aggregate and nano-alumina particles evenly, add water and stir into a slurry; add ultra-high molecular weight polyethylene short fibers and graphene nanosheets into the mixture and stir evenly.
[0046] Moulding: prepare the mould, apply release agent, pour the mixed material into the mould, use a vibrating rod to remove air bubbles and ensure the material is dense.
[0047] Initial curing: Leave it at 20-25℃ for 24 hours for initial curing.
[0048] Wet curing: After initial curing, carry out wet curing for 7 days.
[0049] High temperature drying: Drying is carried out at 60°C to ensure that the moisture in the material is completely evaporated and to improve the hardness and toughness of the material.
[0050] Polyurethane coating treatment: Apply 0.7-1mm thick polyurethane coating evenly on the surface of the material and cure it at room temperature for 48 hours.
[0051] Example 3 Material composition Basic material: High-strength cement-based concrete, as the main structural carrier.
[0052] Reinforcement material: Ultra-high molecular weight polyethylene short fiber (UHMWPE), which improves the toughness and protective properties of the material, and the added amount is 0.1% of the weight of concrete.
[0053] Nano-alumina particles: used to enhance the material's compressive and penetration resistance.
[0054] Graphene nanosheets: Improve the conductivity, explosion resistance and heat resistance of materials.
[0055] Polyurethane coating: used for external coating to prevent the intrusion of moisture and corrosive substances.
[0056] Preparation process Raw material preparation: Select high-strength cement and aggregate, and weigh appropriate amounts of ultra-high molecular weight polyethylene short fibers, nano-alumina particles and graphene nanosheets.
[0057] Mixing process: Mix cement, aggregate and nano-alumina particles evenly, add water and stir into a slurry; add ultra-high molecular weight polyethylene short fibers and graphene nanosheets into the mixture and stir evenly.
[0058] Moulding: prepare the mould, apply release agent, pour the mixed material into the mould, use vacuum extraction equipment to remove bubbles and ensure the material is dense.
[0059] Initial curing: Leave it at 20-25℃ for 24 hours for initial curing.
[0060] Wet curing: After initial curing, carry out wet curing for 7 days.
[0061] High temperature drying: Drying is carried out at 55°C to ensure that the moisture in the material is completely evaporated and to improve the hardness and toughness of the material.
[0062] Polyurethane coating treatment: Apply 0.6-1mm thick polyurethane coating evenly on the surface of the material and cure it at room temperature for 48 hours.
[0063] Test standards and data Compressive strength test According to GB / T 50081-2019 standard, the compressive strength test was carried out using a compression testing machine. The compressive strength of composite materials with different formulations was tested within 28 days.
[0064] Example 1: The compressive strength after 28 days is 45 MPa.
[0065] Example 2: The compressive strength after 28 days is 42 MPa.
[0066] Example 3: The compressive strength after 28 days is 40 MPa.
[0067] Tensile strength test According to GB / T 50081-2019 standard, tensile strength test was carried out using a tensile testing machine. The tensile strength of composite materials with different formulations was tested within 28 days.
[0068] Example 1: The tensile strength after 28 days is 4.5 MPa.
[0069] Example 2: The tensile strength after 28 days is 4.2 MPa.
[0070] Example 3: The tensile strength after 28 days is 4.0 MPa.
[0071] Durability Test According to GB / T 50081-2019 standard, durability tests are carried out to simulate the durability of materials under different environmental conditions.
[0072] Example 1: After 200 freeze-thaw cycles, the compressive strength retention rate is 92%.
[0073] Example 2: After 200 freeze-thaw cycles, the compressive strength retention rate is 89%.
[0074] Example 3: After 200 freeze-thaw cycles, the compressive strength retention rate is 87%.
[0075] Impact resistance test According to GB / T 50081-2019 standard, an impact testing machine was used to test the impact resistance of composite materials with different formulations.
[0076] Example 1: The impact energy is 20 J and there is no obvious crack on the surface.
[0077] Example 2: The impact energy is 18 J, and there are no obvious cracks on the surface.
[0078] Example 3: The impact energy is 15 J, and there are no obvious cracks on the surface.
[0079] Experimental verification Bulletproof test Simulate the impact of a 12.7mm armor-piercing incendiary bullet to test the bulletproof performance of composite materials with different formulations.
[0080] Example 1: The material thickness is 100 mm, and no penetration occurs, showing excellent anti-penetration ability.
[0081] Example 2: The material thickness is 80 mm, and slight penetration occurs, and good anti-penetration ability is not shown.
[0082] Example 3: The material thickness is 60 mm, penetration occurs, and good anti-penetration ability is not shown.
[0083] Explosion-proof test Simulate 4kg TNT explosion to test the explosion-proof performance of composite materials with different formulations.
[0084] Example 1: There are no obvious cracks or peeling on the surface of the material, and the anti-explosion performance is excellent.
[0085] Example 2: Tiny cracks appear on the surface of the material, and the anti-explosion performance is good.
[0086] Example 3: Slight peeling occurs on the surface of the material, and the anti-explosion performance is good.
[0087] Through the above test data and experimental verification, it can be seen that the composite materials with different formulations perform well in terms of strength, bulletproof and explosion-proof properties, and Example 1 can best meet the design requirements and safety standards.
[0088] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A bulletproof and explosion-proof composite material, characterized in that: Includes the following ingredients: Basic materials: high-strength cement-based concrete, as the main structural carrier; Reinforcement material: Ultra-high molecular weight polyethylene short fiber (UHMWPE), which improves the toughness and protective properties of the material; Nano-alumina particles: used to enhance the material's compressive and penetration resistance; Graphene nanosheets: used to improve the conductivity, explosion resistance and heat resistance of materials; Polyurethane coating: used for external coating to prevent the intrusion of moisture and corrosive substances.
2. The bulletproof and explosion-proof composite material according to claim 1, characterized in that: The added amount of the ultra-high molecular weight polyethylene short fibers is 0.3% of the weight of the concrete.
3. The bulletproof and explosion-proof composite material according to claim 1, characterized in that: The length of the ultra-high molecular weight polyethylene short fibers is 5-10 mm.
4. The bulletproof and explosion-proof composite material according to claim 1, characterized in that: The nano-alumina particles are uniformly dispersed in the concrete.
5. The bulletproof and explosion-proof composite material according to claim 1, characterized in that: The added amount of the graphene nanosheets is 0.05% to 0.1% of the weight of the concrete.
6. The process for preparing a bulletproof and explosion-proof composite material according to claim 1, characterized in that: The following steps are involved: S1. Raw material preparation: select high-strength cement and aggregate, weigh appropriate amounts of ultra-high molecular weight polyethylene short fibers, nano-alumina particles and graphene nanosheets; S2, mixing process: mix cement, aggregate and nano-alumina particles evenly, add water and stir into a slurry; add ultra-high molecular weight polyethylene short fibers and graphene nanosheets into the mixture and stir evenly; S3, mold forming: prepare the mold, apply the release agent, pour the mixed material into the mold, vibrate and exhaust, and ensure the material is dense; S4. Preliminary curing: Leave to stand at 20-25℃ for 24 hours for preliminary curing; S5. Wet curing: After initial curing, carry out wet curing for 7 days; S6, high temperature drying: drying at 50°C; S7. Polyurethane coating treatment: Apply a 0.5-1mm thick polyurethane coating evenly on the surface of the material and cure it at room temperature for 48 hours.
7. The process for preparing a bulletproof and explosion-proof composite material according to claim 6, characterized in that: The mold forming process includes vibrating the mold using a vibration table to remove air bubbles from the material.
8. The process for preparing a bulletproof and explosion-proof composite material according to claim 6, characterized in that: The ambient humidity is maintained during the wet curing process to improve the strength and durability of the material.
9. The process for preparing a bulletproof and explosion-proof composite material according to claim 6, characterized in that: The high temperature drying process ensures that the moisture in the material is completely evaporated, thereby improving the hardness and toughness of the material.
Citation Information
Patent Citations
Ultra-high molecular weight polyethylene fiber concrete and preparation method thereof
CN103819155A
Ultrahigh-performance cement-based H-shaped profile
CN104018619A
High-strength concrete and preparation process thereof
CN112759324A
Ultra-high performance concrete as well as preparation method and application thereof
CN116217178A
Concrete excellent in explosion resistance
JP2006290722A
Cited By
Lightweight high-strength bulletproof and blastproof fiber concrete and preparation method thereof
CN122852062A